THE EFFECT OF ACUPRESSURE THERAPY ON INCREASING BREAST MILK PRODUCTION DURING THE POSTPARTUM PERIOD IN 2023 - ayudita, ayudita -; indah gasela, indah gasela - (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2024)
Based on WHO data, that only 44% of newborns in the world get breast milk within the first hour from birth, there are still a few babies under the age of 6 months who are exclusively breastfed. The 2020 National Basic Health Research (Riskesdas) revealed that in Indonesia with a prevalence of 65.7% and the Coverage of IMD babies in Bangka Belitung province was 77.57%, down compared to 2019 (80.11%). One effort that can be used to increase milk production is using the acupressure technique. The purpose of this study was to determine the effect of acupressure therapy on increasing milk production in postpartum mothers. The design uses a quasi-experimental method with pretest and posttest design without control group. The sampling technique used purposive sampling with the number of respondents 20 postpartum. Univariate and bivariate data analysis. The results showed that p value is 0,000 (p < 0,05) on t-test. This proves that there is a significant difference in increasing milk production in postpartum mothers between before and after acupressure therapy. It is recommended for midwives to perform acupressure as a complement in postnatal midwifery care regarding the problem of increasing milk production in postpartum mothers.